Post common envelope binaries from SDSS: II: Identification of 9 close binaries with VLT/FORS2 - Schreiber, M. R.; Gänsicke, B. T.; Southworth, J.; Schwope, A. D.; Koester, D. (Astronomy and astrophysics (Berlin), 2008)
Context. Post common envelope binaries (PCEBs) consisting of a white dwarf and a main sequence star are ideal systems to use to calibrate current theories of angular momentum loss in close compact binary stars. The potential held by PCEBs for further development of close binary evolution could so far not be exploited due to the small number of known systems and the inhomogeneity of the sample. The Sloan Digital Sky Survey is changing this scene dramatically, as it is very efficient in identifying white dwarf/main sequence (WDMS) binaries, including both wide systems whose stellar components evolve like single stars and- more interesting in the context of close binary evolution-PCEBs. Aims. We pursue a large-scale follow- up survey to identify and characterise the PCEBs among the WDMS binaries that have been found with SDSS. We use a two-step strategy with the identification of PCEBs among WDMS binaries in the first phase and orbital period determinations in the second phase. Here we present first results of our ESO-VLT/FORS2 pilot study that targets the identification of the PCEBs among the fainter (}{\scriptstyle sim} similar to 18.5$ g similar to \stackrel{>}{\scriptstyle sim} similar to 18.5) SDSS WDMS binaries. Methods. From published SDSS catalogues we selected 26 WDMS binaries to be observed with ESO-VLT/FORS2 in service mode. The design of the observations was to get two spectra per object separated by at least one night. We used the NA I lambdaλ8183.27, 8194.81 doublet to measure radial velocity variations of our targets and a spectral decomposition/fitting technique to determine the white dwarf effective temperatures and surface gravities, masses, and secondary star spectral types for all WDMS binaries in our sample. Results. Among the 26 observed WDMS binaries, we find 9 strong PCEB candidates showing clear (≥3σ) radial velocity variations, and we estimate the fraction of PCEBs among SDSS WDMS binaries to be 35±12%. We find indications of a dependence of the relative number of PCEBs among SDSS WDMS binaries on the spectral type of the secondary star. These results are subject to small number statistics and need to be confirmed by additional observations. Using Magellan- Clay/LDSS3, we measured the orbital periods of two PCEB candidates, SDSS J1047+0523 and SDSS J1414-0132, to be 9.17 h and 17.48 h, respectively. Conclusions. This pilot study demonstrates that our survey is highly efficient in identifying PCEBs among the SDSS WDMS binaries, and it will indeed provide the observational parameters that are needed to constrain the theoretical models of close binary evolution.